An EST resource for cassava and other species of Euphorbiaceae - Anderson, J.W.; Delseny, M; Fregene, Martin A.; Jorge, V.; Mba, C; López, C.E.; Restrepo, S.; Soto Suárez, M.; Piegu, B; Verdier, Valerie M.; Cooke, R.G.; Tohme, Joseph M.; et al. (Springer, 2004)
Cassava (Manihot esculenta) is a major food staple for nearly 600 million people in Africa, Asia, and Latin America. Major losses in yield result from biotic and abiotic stresses that include diseases such as Cassava Mosaic Disease (CMD) and Cassava Bacterial Blight (CBB), drought, and acid soils. Additional losses also occur from deterioration during the post-harvest storage of roots. To help cassava breeders overcome these obstacles, the scientific community has turned to modern genomics approaches to identify key genetic characteristics associated with resistance to these yield-limiting factors. One approach for developing a genomics program requires the development of ESTs (expressed sequence tags). To date, nearly 23000 ESTs have been developed from various cassava tissues, and genotypes. Preliminary analysis indicates existing EST resources contain at least 6000–7000 unigenes. Data presented in this report indicate that the cassava ESTs will be a valuable resource for the study of genetic diversity, stress resistance, and growth and development, not only in cassava, but also other members of the Euphorbiaceae family.